Behenic acid protects the testosterone cycle and prevents the sperm apoptosis and protein loss in phthalate exposure by inhibiting oxidative stress and stimulating ATPase activity - Khaled M.M. Koriem; Mayar S.R. El-Masry (Toxicology Reports)
Background: Plastic products use phthalate to enhance their flexibility, transparency, and stability, while behenic acid is a carboxylic acid with antioxidant activity. Objectives: This study evaluates whether behenic acid can protect the testosterone cycle and prevent the sperm apoptosis and protein loss in phthalate-treated male rats. Methods: There were 36 male albino rats in all, divided into six equal sets of six rats each: control, behenic acid (13 g/kg), behenic acid (26 g/kg), diethyl phthalate (10 mg/kg), behenic acid (13 g/kg) + diethyl phthalate (10 mg/kg), and behenic acid (26 g/kg) + diethyl phthalate (10 mg/kg)-treated groups. Measurements were made of serum male hormones, sex hormone-binding globulin, sodium/potassium ATPase, superoxide dismutase, glutathione, glucose-6-phosphate dehydrogenase, 3β-hydroxysteroid dehydrogenase, protein, and cholesterol in the testis, as well as malondialdehyde in the sperm, testis, and hypothalamus. Sperm monoclonal proliferating antibody Ki-67, sperm counts, motility, and abnormalities were measured. Results: Oral administration of diethyl phthalate increased malondialdehyde, serum follicle stimulating hormone, sex hormone binding globulin, luteinizing hormone, glucose-6-phosphate dehydrogenase, 3β-hydroxysteroid dehydrogenase, cholesterol, total protein, sperm abnormality, and the percentage of spermatogonia, first spermatocyte, second spermatocyte, and spermatid in the testis. Superoxide dismutase, glutathione, serum testosterone and dehydroepiandrosterone sulphate, sperm count and motility, and sodium/potassium-ATPase activity were all reduced. Additionally, all of the previously described parameters reverted to near control values after receiving two doses of behenic acid in phthalate-treated rats; a higher dose of behenic acid had a more effective effect than a lower dose. Conclusion: behenic acid can protect the testosterone cycle and prevent the sperm apoptosis and protein loss in phthalate-treated male rats by inhibiting oxidative stress and stimulating ATPase activity.